Role of Family in Increasing Self Efficacy Patient Heart Failure - Suwardha Yunus; Ariyanti Saleh; Takdir Tahir (Universitas Muhammadiyah Semarang, 2020)
Heart failure is a collection of clinical and complex problems that can be life-threatening due to structural abnormalities or heart dysfunction. In both developed and developing countries. The role of the family is needed in the handling of HF patients to prevent the occurrence of mortality and morbidity, also has an impact on self-efficacy. This review identifies the role of the family in increasing self-efficacy. Metode of discursive with a literature review of several articles related to the 2010-2019 scientific search using PubMed, Cochran, ScienceDirect, google scholar, there are 117 articles. Article exclusion is not in English and not in full text. The remaining 36 articles are. The inclusion of articles according to the study were 5 articles. Results are obtained 5 articles consisting of 1 article discussing the role of the family as caregivers for self-care, 2 articles discuss increasing the self-efficacy of HF patients and their treatment. And 2 articles discuss the role of the family as a supporter of HRQoL. The role of the family in the care of patients with HF as caregivers fulfills the patient's self-care, and affect the patient's self-efficacy to improve the quality of life.